Kreativitas Pembuatan Media Pembelajaran Big Book Pada Guru-Guru RA Di Kecamatan Medan Maimun - Juli Maini Sitepu; Mawaddah Nasution (Universitas Muhammadiyah Sumatera Utara, 2018)
The creativity of making big book learning media for RA teachers in Medan Maimun District is done because there are many RA teachers in Medan Maimun sub-district who do not yet have the ability to make the right learning media so that this will also affect the language skills of RA Students. Other than that, in stories telling and teaching languages, there are still many teachers who use small story books that make learning less interesting. The lack of ability to make the right learning media is due to the education background of RA teachers in Medan Subdistrict, but on the average only graduates of Public and Undergraduate Schools are non PAUD / Non PGRA. The method used in this PKM is by holding a training program for making big book learning media for RA teachers and in collaboration with the Association of Guru Raudhatul Athfal, Medan District Maimun. RA teachers are introduced to the types of learning media and are taught how to create big book learning media. And than monitoring is carried out by the proposer team until the partners develop themselves. At the end of the program it is expected that RA teachers can make their own big book learning media more creative and interesting so that they can be used in the learning process. RA teachers are proficient at making big book learning media, later partners can make this skill a more selling point.